2022
DOI: 10.1111/1750-3841.16283
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression involved in starch synthesis pathway genes reveal various starch characteristics of seed and rhizome in lotus (Nelumbo Nucifera)

Abstract: Lotus (Nelumbo nucifera) is one of the main aquatic vegetables in China. Its seed and rhizome are main edible parts which are rich in starch. Preliminary experiments of starch contents revealed that seed and rhizome expressed great differences in amylose and amylopectin contents. The rhizomes have higher amylopectin content, while the seeds have higher amylose content. In this study, we have estimated 16 varieties of lotus seeds and found that the amylose content of lotus seeds ranged from 30% to 50%, with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Lotus root is an underwater rhizome with a unique, compact texture, and it is rich in essential nutrients (Yi et al., 2022; Zhu et al., 2022). In our preliminary investigation, which aimed to find out which food ingredients are more likely to produce acrylamide during cooking, it was found that lotus root stands out with exceptionally high levels of acrylamide production.…”
Section: Introductionmentioning
confidence: 99%
“…Lotus root is an underwater rhizome with a unique, compact texture, and it is rich in essential nutrients (Yi et al., 2022; Zhu et al., 2022). In our preliminary investigation, which aimed to find out which food ingredients are more likely to produce acrylamide during cooking, it was found that lotus root stands out with exceptionally high levels of acrylamide production.…”
Section: Introductionmentioning
confidence: 99%
“…ADP-Glucose is then converted by ADP glucose pyrophosphorylase (AGPase) into hexose phosphate (G1P and G6P), leading to further ADP-glucose synthesis ( Fig. 2 ) ( Zhu et al, 2022 ). Finally, ADP-glucose produces amylopectin through the activities of starch isomerase, starch branching enzyme, and soluble starch synthase, while another portion is transformed into amylose by granule-bound starch synthase and stored in endosperm cells ( Lee et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%